2004
DOI: 10.1177/0731684404039797
|View full text |Cite
|
Sign up to set email alerts
|

Impactor Mass Effects in Glass–Epoxy Composites Subjected to Repeated Drop Tests

Abstract: Experimental studies were carried out to understand the impactor mass effects on glass–epoxy composites using an instrumented impact machine (DYNATUP 8250) under low-velocity test conditions. Repeated drop tests were carried out at pre-determined energy levels for selective mass height combinations. Number of drops to failure (Nf) was chosen as the damage criterion. Analysis of test results clearly showed that, at low incident energies, heavier impactors caused more damage to the laminates as reflected by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The number of drops to failure of laminates reduces with heavier impactors at low impact energies. Further, the effect of impactor mass was observed to diminish as the incident impact energy increased [69].…”
Section: Impactor Geometry and Mass Effectsmentioning
confidence: 96%
“…The number of drops to failure of laminates reduces with heavier impactors at low impact energies. Further, the effect of impactor mass was observed to diminish as the incident impact energy increased [69].…”
Section: Impactor Geometry and Mass Effectsmentioning
confidence: 96%
“…The effect of impactor mass on the response of the composites impacted was investigated by Sugun and Rao. 11 They found that heavier impactor caused more damage to the laminates as reflected by their lower number of drops to failure. They continued their studies with various materials such as glass/epoxy, carbon/epoxy, and Kevlar/epoxy while impactor mass was kept constant and incident energies ranged from 3.5 J to 15 J.…”
Section: Introductionmentioning
confidence: 99%
“…Although repeated impacts are not uncommon in real-world applications of composites [9,10], there are not many studies in the literature addressing that, either numerically-or experimentally-based, as most focus on multiple hits at the same point [11]. The studies on the repeated impact behavior of composites mostly concern repeated impact at the same location by considering different impactor or target features, such as impactor geometry [12][13][14] and mass [15], reinforcement type [16][17][18][19], laminate thickness [17,20], and stacking sequence [21,22]. Atas et al [23] investigated the effect of thickness on the repeated low-velocity impact response of E-glass/epoxy composites reporting the energy profiling diagram and the perforation limit.…”
Section: Introductionmentioning
confidence: 99%